Meeting report: the inaugural muscle biology and cachexia conference at the University of Houston, May 18-20, 2025, Houston, Texas, USA - Chen, Jingjuan; Brotto, Marco; Darabi, Radbod; Kumar, Ashok (Frontiers in Physiology, 2025)
In May 2025, the University of Houston (UH) hosted the inaugural Muscle Biology and Cachexia conference, organized by Drs. Ashok Kumar and Radbod Darabi. The conference attracted nearly 300 participants, including established scientists, early-career researchers, and students from across the United States, Canada, Italy, Singapore, and Turkey. Research was presented through a combination of oral presentations and poster sessions. The conference was driven by the increasing interest in skeletal and cardiac muscle biology and cancer cachexia among institutions at the Texas Medical Center and surrounding universities. It served as a platform to promote knowledge exchange and foster collaboration within this growing scientific community. The conference was supported by the UH College of Pharmacy (UHCOP), Division of Research (DOR), Drug Discovery Institute (DDI), and the Department of Pharmacological and Pharmaceutical Sciences (PPS). In conjunction with the conference, UH announced the formation of the Institute of Muscle Biology and Cachexia (IMBC). The IMBC aims to strengthen collaborative research efforts and enhance understanding of the molecular and signaling pathways that regulate muscle physiology and disease.